The Role of Vahid Abdullayev's Scientific Activity in the Development of Literary Schools - Rahmatova Dilfuza Ahmedovna (International Journal on Integrated Education, 2022)
The article reflects the role of the candidate and doctoral dissertations of academician Vahid Abdullayev in the development of our literature, the fact that the scientific research of the scientist serves today's requirements.